Strength Profile of the Inner Nankai Accretionary Prism at IODP Site C0002. Issue 19 (16th October 2019) - Kitamura, Manami; Kitajima, Hiroko; Sone, Hiroki; Hamada, Yohei; Hirose, Takehiro
Abstract: The strength of accretionary prisms is important for understanding their formation and the generation of earthquakes along the underlying plate boundary faults. We establish a continuous depth profile of rock strength and possible ranges of the minimum and maximum horizontal stresses ( S hmin and S Hmax ) based on indentation tests on cuttings samples at the Integrated Ocean Drilling Program (IODP) Site C0002 in the Nankai accretionary prism. The rock strength (i.e., differential stress) increases with depth from 5.1 and 11.0 MPa at 975 meters below the seafloor (mbsf) to 22.8 and 59.6 MPa at 3005 mbsf in normal and reverse faulting regimes, respectively. The minimum value of S hmin and the maximum value of S Hmax range from 33.2 and 49.4 MPa at 975 mbsf to 57.1 and 139.6 MPa at 3005 mbsf, respectively. Our estimated strength, in combination with Coulomb wedge model, may improve understanding of the evolution of accretionary prisms. Key Points: Strength of the inner Nankai accretionary prism is estimated from indentation tests on cuttings Our estimation constrains the ranges of possible maximum and minimum principal stresses, which are limited by rock strength and loading stress regimes Differential stress reaches 57.1 and 139.6 MPa at 3 km below seafloor for the normal and reverse faulting stress regimes, respectively